2009
DOI: 10.1111/j.1365-2648.2009.04975.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based practice‐focused interactive teaching strategy: a controlled study

Abstract: The EBP-focused interactive teaching strategy was effective in improving the knowledge and use of EBP among nursing students but not attitudes toward or future use of EBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
11

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 36 publications
3
66
0
11
Order By: Relevance
“…This study supports others in emphasising the importance of lecturers in creating and leading a research-based culture and positive attitude to research (Ilott and Bury 2002;Kajermo et al, 2008;Koehn and Lehman, 2008;Kim et al, 2009). Although the numbers of lecturers submitted to the recent national Research Assessment Exercise (RAE) are small, progress in their research capacity over previous years has been good (Corbyn, 2009).…”
Section: Increasing Capability and Capacity In Researchsupporting
confidence: 74%
See 2 more Smart Citations
“…This study supports others in emphasising the importance of lecturers in creating and leading a research-based culture and positive attitude to research (Ilott and Bury 2002;Kajermo et al, 2008;Koehn and Lehman, 2008;Kim et al, 2009). Although the numbers of lecturers submitted to the recent national Research Assessment Exercise (RAE) are small, progress in their research capacity over previous years has been good (Corbyn, 2009).…”
Section: Increasing Capability and Capacity In Researchsupporting
confidence: 74%
“…In 2007, in the United Kingdom (UK), the UK Clinical Research Collaborative (UKCRC) reported a 'sharp divide' in nursing, between educators and researchers on the one hand, and clinical practitioners on the other, as witnessed in both the USA and Australia (Dunn and Yates, 2000). As Kim et al (2009) acknowledge, the role of nurse educators is pivotal in preparing graduating students with the skills, knowledge and a positive attitude to research. They argue that teachers should adopt innovative learning and teaching strategies and arguably, should demonstrate credibility in the research field in order to influence and motivate their students.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Many health care institutions have conducted educational programs to provide nurses and other health care professionals with EBP knowledge and skills (Cullen and Titler, 2004;Hart et al, 2008;Kim et al, 2009). In the past decade, tertiary education institutions and universities have introduced undergraduate and postgraduate courses (Kaplan Jacobs et al, 2003;Damen et al, 2011;Badger et al, 2012) to equip students with the appropriate knowledge and skills to successfully implement EBP principles.…”
Section: Teaching Ebp To Postgraduate Health Professionalsmentioning
confidence: 99%
“…Esta estrategia docente interactiva fue diseñada en base a la literatura reciente sobre el aprendizaje de esta competencia para alumnos tanto de medicina como enfermería [139][140][141][142][143][144][145][146][147][148][149][150][151] . Así, se compone de forma específica de dos horas teóricas de Práctica Basada en la Evidencia en la que se sumerge al alumno en:…”
Section: Variable Intervenciónunclassified